2002
DOI: 10.1046/j.1523-1755.2002.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from release of ureteral obstruction in the rat: Relationship to nephrogenesis

Abstract: In the period immediately following nephrogenesis, the kidney is particularly susceptible to long-term injury from temporary UUO. This suggests that a delay in relief of significant ureteral obstruction should be avoided if diagnosed in the perinatal or neonatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 55 publications
3
69
0
2
Order By: Relevance
“…We reported previously that renal maturation is delayed by chronic complete UUO. This includes persistence of an immature pattern of glomerular maturation (7,8), microvascular renin distribution (7), and of tubular (25) and interstitial markers (11,38). In the present study, we showed that glomerular maturation is also delayed in the neonatal rat following partial UUO.…”
Section: Discussionsupporting
confidence: 52%
“…We reported previously that renal maturation is delayed by chronic complete UUO. This includes persistence of an immature pattern of glomerular maturation (7,8), microvascular renin distribution (7), and of tubular (25) and interstitial markers (11,38). In the present study, we showed that glomerular maturation is also delayed in the neonatal rat following partial UUO.…”
Section: Discussionsupporting
confidence: 52%
“…Decreases in urinary K + levels in the obstructed kidney likely reflect a reduced GFR rate and are also a product of urinary dilution [24]. Cl -excretion should be expected to increase in both the contralateral and obstructed kidneys, due to natriuresis.…”
Section: Discussionmentioning
confidence: 99%
“…Such short-term obstruction does not induce TBM destruction and EMT ( Figure 5). However, renal structure and function is permanently impaired when relief of obstruction occurs after a sustained injury (more than 5 days) (44)(45)(46), a time when TBM integrity is impaired and EMT is prominent. Hence, EMT not only actively participates in the pathogenesis of interstitial fibrogenesis, but also may function as an intrinsic determinant for irreversible progression of chronic fibrotic lesions.…”
Section: Discussionmentioning
confidence: 99%